Development of a Financial Literacy Book, "Good and Bad Character Augmented Reality," for Early Childhood - Suzanti, Lizza; Fitriasari, Novi Sofia; Widjayatri, Rr Deni; Soflianti, Siti Dela; Utari, Gita Cahya; Bulan, Dwi Via Cahya; Burairoh, Siti Annisa; Fajriah, Awalia (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
Financial literacy education needs to be instilled from an early age through attractive media so that it is internalized and to form managing finances habits in the future. Augmented Reality (AR) technology is an alternative since it is in the 3D form to visualize abstract concepts into concrete ones. This study aims to develop a financial literacy book with augmented reality technology, "Good and Bad Character AR." This book instills financial knowledge and experience for children in forming good character and habits. The method used in this study was Design Development (DD), with an analysis model of design, development, implementation, and evaluation (ADDIE). Participants were material and media experts and users (teachers and children aged 5-6 years) at the UPI Campus Labschool Kindergarten in Serang. Validation was carried out by media experts, material experts, two teachers, and five children. The analysis results demonstrated that the financial literacy book "Good and Bad Character AR" was feasible for educators to use in increasing early childhood financial literacy based on the assessment of material experts of 85.33% and media experts of 87%, with a very good category. Meanwhile, the user response came from two teachers respectively at 98.33 and 90%, considered very good in terms of the attractiveness of the content, ease of use, and the children's enthusiasm during learning. In addition, of the five children, 92% were obtained, indicating a very good response. It indicated that AR technology is feasible and potentially used in early childhood learning.